Detection and characterization of Cryptosporidium species and genotypes in three chicken production systems in Brazil using different molecular diagnosis protocols - Santana, Bruna Nicoleti [UNESP]; Kurahara, Brayan [UNESP]; Nakamura, Alex Akira; da Silva Camargo, Vinícius [UNESP]; Ferrari, Elis Domingos [UNESP]; da Silva, Giane Serafim; Nagata, Walter Bertequini [UNESP]; Meireles, Marcelo Vasconcelos [UNESP] (Elsevier, 2018)
The objective of this study was to determine the occurrence of Cryptosporidium spp. in domestic chickens raised in different chicken production systems in Brazil using three nested PCR protocols. The purification and concentration of oocysts present in 190 fecal samples from chickens raised in extensive, semi-intensive and intensive production systems were accomplished by centrifugal flotation in Sheather's solution and were followed by the extraction of genomic DNA. The detection and molecular characterization of Cryptosporidium species and genotypes were performed using three nested polymerase chain reaction (nested PCR) protocols targeting the 18S rRNA gene followed by sequencing of the amplified fragments. Subgenotyping of C. meleagridis was performed using a nested PCR reaction targeting the gp60 gene. Sample identified as Cryptosporidium sp. genetically similar to Cryptosporidium xiaoi and Cryptosporidium bovis by 18S rRNA gene sequencing were further analyzed by nested PCR targeting the actin gene and subsequent sequencing of the amplified fragment. Positive amplification for Cryptosporidium spp. was observed in 12.6% (24/190) of the samples, including C. baileyi (9.8%; 18/190), C. meleagridis (0.5%, 1/190), C. parvum (2.1%; 4/190) and Cryptosporidium sp. (0.5%; 1/190). Subgenotyping of C. meleagridis revealed the presence of the zoonotic subtype IIIgA23G3R1. Sequencing of the 18S rRNA gene and the actin gene fragments revealed a Cryptosporidium genotype in an extensive poultry system genetically related to C. xiaoi and C. bovis. There was no significant difference in the frequency of positive results obtained by the three nested PCR protocols (p > 0.05); additionally, the agreement obtained by Kappa index ranged from substantial (0.70) to almost perfect (0.9).
Keywords: Brazil; Cryptosporidiosis; Diagnosis; Domestic chicken; Molecular characterization